Neuroprotective Potential of Non-Digestible Oligosaccharides: An Overview of Experimental Evidence - Gangaraju Divyashri; Bindu Sadanandan; Kotamballi N Chidambara Murthy; Kalidas Shetty; Kumari Mamta (Frontiers Media S.A., 2021)
Non-digestible oligosaccharides (NDOs) from dietary sources have the potential as prebiotics for neuroprotection. Globally, diverse populations suffering from one or the other forms of neurodegenerative disorders are on the rise, and NDOs have the potential as supportive complementary therapeutic options against these oxidative-linked disorders. Elevated levels of free radicals cause oxidative damage to biological molecules like proteins, lipids, and nucleic acids associated with various neurological disorders. Therefore, investigating the therapeutic or prophylactic potential of prebiotic bioactive molecules such as NDOs as supplements for brain and cognitive health has merits. Few prebiotic NDOs have shown promise as persuasive therapeutic solutions to counter oxidative stress by neutralizing free radicals directly or indirectly. Furthermore, they are also known to modulate through brain-derived neurotrophic factors through direct and indirect mechanisms conferring neuroprotective and neuromodulating benefits. Specifically, NDOs such as fructo-oligosaccharides, xylo-oligosaccharides, isomalto-oligosaccharides, manno-oligosaccharides, pectic-oligosaccharides, and similar oligosaccharides positively influence the overall health via various mechanisms. Increasing evidence has suggested that the beneficial role of such prebiotic NDOs is not only directed towards the colon but also distal organs including the brain. Despite the wide applications of these classes of NDOs as health supplements, there is limited understanding of the possible role of these NDOs as neuroprotective therapeutics. This review provides important insights into prebiotic NDOs, their source, and production with special emphasis on existing direct and indirect evidence of their therapeutic potential in neuroprotection.